The Impact of Online Consumer Reviews on Purchase Intentions: A Study of Cosmetic Product Buyers on E-Commerce Platforms in Nepal - Pudasaini, Pooja; Dangol, Jeetendra (Journal of Business and Social Sciences Research, 2024)
This study aims to assess the effects of online consumer reviews on the cosmetic purchasing behaviour in Nepal, based on 384 responses from individuals aged 15 to 60. Correlation analysis revealed positive associations (moderate, weak, or strong) with customer purchasing plans. Regression analysis helped determine the alignment of variables using P-values. The outcome revealed that review quality and quantity have a strong relationship with purchasing intentions, thus supporting the hypothesis. In contrast, source credibility and valence did not show a significant impact. Influencers, such as bloggers and celebrities, played a mediating role, affecting purchase decisions through their critiques. This underscores the importance of positive reviews, and the trust customers place in influencers. For marketing companies, it is crucial to carefully select brand influencers to effectively leverage potential customers’ buying decisions.